Ransomware protection using the moving target defense perspective. (September 2019) - Lee, Suhyeon; Kim, Huy Kang; Kim, Kyounggon
Highlights: We analyzed the ransomware attack process in four phases which are receiving a key from attacker's server, finding target files, generating an encryption key, and encrypting target files. Our approach can be a "game changer" to respond to ransomware; we provide a brand-new preventive measure beyond traditional detection measures by randomly and continuously changing file extensions. To the best of our knowledge, this approach is the first preemptive measure to respond to ransomware by applying the Moving Target Defense method. Experiments with our approach have shown that we can effectively protect important files from ransomware attacks. In our experiment, we could protect important files from 141 of the 143 ransomware samples in four ransomware families. We consider usability and compatibility for most personal computer environments. Our approach requires minimal computational power so as not to result in performance degradation; Also, it does not need to deploy additional security software to apply the proposed method. Abstract: Ransomware has become the most dangerous threat today because of its unique and destructive characteristics. Ransomware encrypts the victim's important files and then requires money to decrypt them. Ransomware has become among the most preferred measures for cybercriminals to earn money. Moreover, the technology for producing ransomware continues to evolve; as a result, it has becomes more difficult to defend. In this study, we analyze major ransomware including WannaCry and propose a method to protect valuable files from existing ransomware. To this end, the moving target defense method is applied by randomly changing the file extensions that ransomware attempts to encrypt. We show that our proposed method can successfully protect files from ransomware. Finally, we present the proposed method which can be reasonably used without performance degradation.